Insurance development in the Arab world: an analysis of the relationship between available domestic retention capacity and the demand for international reinsurance - Ali, Abdul Zahra Abdullah (1984)
This thesis is concerned with an examination of the available domestic retention capacity and the demand for international reinsurance in the Arab World. The study has been broken down into the following basic components: